O fantástico, o maravilhoso e o estranho na composição da figura do narrador em Castelli di rabbia, de Alessandro Baricco - Graziano, Pedro Henrique Pereira [UNESP] (2017)
The goal of this research is to clarify how the literary modes Fantastic, Wonderful and Strange, as defined by Ceserani (2006), are important for the composition and valorization of the figure of the narrator in contemporary society in Alessandro Baricco‘s Castelli di rabbia (1991). It‘s believed that the narrator in this work is the one took into consideration by Walter Benjamin (1996), which would be an almost extinct decadent figure due to the arrival of the modernity and the decline of collective experience. The Italian author of this work builds a narrative in which there are several smaller narratives that compose the novel. Each one of these smaller narratives happens inside of a fantastic universe, in which the above-quoted literary modes take place alternately. To study these literary modes, authors such as Furtado (1980), Ceserani (2006), Bessière (1974), and also some considerations of Todorov (1975), pioneering author in this field of study, will be taken into consideration. Each one of the smaller stories narrated have in common the fact that they approach a life goal of some character inside of an imaginary universe, in which the rules of our natural world no longer exist. All these goals are apparently impossible and unreachable, and, however, the characters insist on pursuing them. The goal of this research is to demonstrate how the yen of accomplishment of these goals and the fact that the characters never lose their faith build a strong dialogue with Walter Benjamin‘s conceptions about the narrator and modernity, given that each character narrates his story as well as the ancient ones that preceded this period, in which, according to Benjamin, the art of narrating is about to disappear. The objective of this study is to make explicit how Alessandro Baricco employs the literary modes Fantastic, Wonderful and Weird to revalorize the narrator, creating allegories based on an imaginary universe. In this universe, the characters narrate and share experiences, as well as the narrator defined by Walter Benjamin does. The allegories built have the goal of creating an association between the act of narrating and the act of resisting to the death of narrative and of literature as art, given that after the arrival of bourgeois modernity, literature in general starts to be sold as merchandise. Therefore, literature loses its advisable character, being an object through which it is possible to share experiences. This causes the loss of ancient literary values.